Islamic Education Strategy Based on the Integration of Local Wisdom for Developing Students Spiritual Character - Alkausar Saragih; Nelvitia Purba; Ismed Batubara; Yeltriana Yeltriana (Fitrah: Journal of Islamic Education, 2025)
Islamic education amid the tide of modernization faces serious challenges in the form of weakening spiritual character and the disconnection of religious values from the local cultural context. This condition calls for an educational approach that is not only normative, but also contextual and rooted in local wisdom. This study aims to identify the Islamic educational values contained in the Sedulur Papat Limo Pancer philosophy and analyze strategies for integrating them into the spiritual character development of students in Nagori Maligas Bayu. This study uses a qualitative approach with a literature study method and a philosophical-contextual analysis of the Sedulur Papat Limo Pancer concept, combined with an Islamic educational perspective. The results show that the Sedulur Papat Limo Pancer philosophy contains Islamic educational values, including purity, sincerity, gratitude, empathy, responsibility, discipline, moral courage, respect for parents, and balance in life. The integration of these values in Islamic education has implications for strengthening the spiritual character of students holistically through a reflective, dialogical, and locally-based approach. This study emphasizes the importance of local wisdom as a strategic resource for the development of relevant and sustainable Islamic education.